Prevalence and chemotherapy of Staphylococcus aureus mastitis in dairy cattle - Asjad Umair Shah; Jawaria Ali Khan; Muhammad Avais; Syed Haider Zaman; Zubir Munir; Safdar Abbas; Mahnoor Tariq; Muneeb ur Rahman; Fiza Tariq; Saqib Nawaz; Dalia Fouad; Aftab Ahmad Anjum; et al. (PLoS ONE, 2025)
This study aimed to isolate and characterize Staphylococcus aureus (S. aureus) from samples of mastitis milk taken from dairy cattle in Punjab’s Narowal District. 200 milk samples were collected aseptically from different dairy herds in the district, including clinical mastitis (CM) and sub-clinical mastitis (SCM) cows. Blood agar and mannitol salt agar were used for S. aureus isolation and identification. Selective media were then used for additional purification. Observations of morphological and biochemical traits verified the existence of S. aureus. Through questionnaire-based surveys, the prevalence of S. aureus mastitis was identified, and risk variables linked to its incidence were evaluated. The findings showed that S. aureus mastitis was prevalent in 42.5% of cases, with sub-clinical cases having a greater incidence (45.8%) than clinical cases (37.5%). Risk factors such as distance from dung pile to stall(m), source of water, dung removal per day, lactation period (weeks), parity, effect of milk yield (L), traumatic injury of udder, housing type, floor type, teat dipping, and bedding type was identified and their relationship to the occurrence of S. aureus mastitis was studied. Tests for antibiotic sensitivity revealed that S. aureus isolates were responsive to gentamycin, ceftiofur, tetracycline, enrofloxacin, and ciprofloxacin but extremely resistant to penicillin and amoxicillin. Additionally, the Somatic Cell Count (SCC) and California Mastitis Test (CMT) were used at different intervals to assess the effectiveness of the medication. Furthermore, compared to other treatment groups, a larger percentage of cure rates was seen in the groups receiving ceftiofur and enrofloxacin. Overall, this study contributes to the development of more effective management methods for S. aureus mastitis in dairy calves by offering insightful information about the condition’s prevalence, risk factors, antibiotic sensitivity, and effectiveness of treatment.